REDUCING UNEMPLOYMENT INCIDENCE FOR ECONOMIC SECURITY IN NIGERIA: THE INTERPLAY OF ENTREPRENEURSHIP EDUCATION AND URGENT SOCIAL INTERVENTION - E. Ekanem, Ekpenyong; E. Emanghe, Emmanuel (British Journal of Marketing Studies, 2014)
Economic security being an ingredient for growth and development, makes no sense if job creation is not an outcome. Hence, this study examined the interplay of entrepreneurship education and urgent social intervention in order to reduce unemployment incidence in Nigeria. This simple descriptive survey design study provided a baseline information for policy-management on education in order to enhance productivity of citizens in Nigeria. Secondary data from National Bureau of Statistics and other data sources were obtained to answer four research questions raised for the study. Data analysis was effected with sample descriptive statistics and tables. Results obtained revealed: high rate of unemployment (across education levels and age groups), low level of entrepreneurship education, high prospects of entrepreneurship education in poverty alleviation and increase employment opportunities; and a tripatriate government intervention in their policies and programmes in order to create employment opportunities for citizens. Therefore, it was recommended that policymakers should emphasize entrepreneurship education at all levels of education while government should invest more on public goods for job opportunities in Nigeria.